Method of removal of colloid iron from groundwater of Western Siberia region by using of carbon dioxide; IFOST 2012; Vol. 1 - Machekhina K. I. Ksenia Igorevna; Shiyan L. N. Lyudmila Nikolaevna; Tropina E. A. Elena Aleksandrovna; Voyno D. Denis (Section 1. Chemical engineering and "Green technology", 2012)
Water objects of Siberia north contain impurities in water in colloid form. The impurities are stable to physical and chemical influence. Search ways of decreasing of natural colloid solutions stability is topical issue. Destruction of colloid particles makes it possible to produce qualitative potable water. In the present work factors influenced on aggregate stability of colloid solutions are represented. It is shown that a disperse phase of natural colloid systems consists of iron and silicium ions and humic organic substances in the ratio 5.6 mg/L:20 mg/L:2.2 mg/L, respectively. Calculated electrokinetic potential of colloid solutions is in the range from -23 up to -32 mV. Stability of colloid iron is studied at the presence of CaCl2 and AlCl3 electrolits. Coagulation thresholds of CaCl2 and AlCl3 are equal to 1.25 mmol/L and 0.0074 mmol/L, respectively. Furthermore, it is shown pH is also influenced on stability ofthe colloid system. When pH of solution is 4.5 colloid iron system coagulates. This fact allows developing a method of removal of colloid iron by temporal decreasing of pH by using of carbon dioxide. This method is ecologically safe and allows simplifying technology of water-preparation due to exceptionof the thin filtration which is used for removal colloid particals. The pH renewal is spontaneous process which is going while carbonization is going. Thermodynamic calculations of reactions describing the destruction mechanism of colloid iron are represented.